The effect of players' standard and tactical strategy on game demands in men's basketball - Ben Abdelkrim, N.; Castagna, C.; El Fazaa, S.; El Ati, J. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to examine the effects of competitive level and team tactic on game demands in men's basketball. Sixteen international-level male basketball players (INPs) and 22 national-level male basketball players (NLPs) were studied during 6 games. Time-motion analysis was performed to track game activities. Game physiological demands were assessed by monitoring heart rate (HR) and blood-lactate concentration. Results showed that INPs sprinted significantly more and performed more high-intensity shuffling than did NLPs (p < 0.05). Game-activity changes and frequency of high-intensity bouts were similar in man-to-man and zone-marking games (1,053 vs. 1,056 and 253 vs. 224, respectively, p > 0.05). Time spent in the maximal (>95% of HRmax) and high-intensity zone (85-95% of HRmax) was greater in the INPs than in the NLPs (17.8 vs. 15.2%, p < 0.01 and 59.1 vs. 54.4%, p < 0.05, respectively). No significant differences in mean HR were evident between man-to-man and zone-marking games (93.3 ± 2.1 vs. 92.8 ± 1.8% of HRmax, p > 0.05). Blood-lactate concentration was higher in the INPs than in the NLPs (6.60 ± 1.22 vs. 5.66 ± 1.19 mmol/L at halftime and 5.65 ± 1.21 vs. 4.43 ± 1.43 mmol/L at full time, p < 0.05). No mean or peak blood-lactate concentration differences resulted between man-to-man and zone-marking games (5.15 ± 1.32 vs. 5.83 ± 1.10 and 5.90 ± 1.25 vs. 6.30 ± 1.27 mmol/L, respectively, p > 0.05). These results suggest an effect of competitive level over game demands in men's basketball. No marking strategy effect was evident. Basketball coaches and fitness trainers should develop the ability to repeatedly perform high-intensity activity during the game. Repeated sprinting and high-intensity shuffling ability should be trained to successfully play man-to-man and zone defense, respectively.